How to write a successful grant application: guidance provided by the European Society of Clinical Pharmacy - OKUYAN, BETÜL (My University, 2023)
Considering a rejection rate of 80-90%, the preparation of a research grant is often considered a daunting task since it is resource intensive and there is no guarantee of success, even for seasoned researchers. This commentary provides a summary of the key points a researcher needs to consider when writing a research grant proposal, outlining: (1) how to conceptualise the research idea; (2) how to find the right funding call; (3) the importance of planning; (4) how to write; (5) what to write, and (6) key questions for reflection during preparation. It attempts to explain the difficulties associated with finding calls in clinical pharmacy and advanced pharmacy practice, and how to overcome them. The commentary aims to assist all pharmacy practice and health services research colleagues new to the grant application process, as well as experienced researchers striving to improve their grant review scores. The guidance in this paper is part of ESCP\"s commitment to stimulate \"innovative and high-quality research in all areas of clinical pharmacy\".
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; FARMAKOLOJİ VE ECZACILIK; Farmakoloji ve Toksikoloji; Yaşam Bilimleri (LIFE); PHARMACOLOGY & PHARMACY; PHARMACOLOGY & TOXICOLOGY; Life Sciences (LIFE); Farmakoloji; Farmakoloji, Toksikoloji ve Eczacılık (çeşitli); Genel Farmakoloji, Toksikoloji ve Eczacılık; Farmakoloji (tıbbi); İlaç Rehberleri; Pharmacy; Pharmacology; Pharmacology, Toxicology and Pharmaceutics (miscellaneous); General Pharmacology, Toxicology and Pharmaceutics; Pharmacology (medical); Drug Guides; Clinical pharmacy; Economics; Funding; Grants; Peer review; Writing; QUESTIONS; SECRETS; ART